The Relationship between Environmental Policy, Community Awareness, and Social Support to Participation in Forest Conservation Programs in West Kalimantan - Loso Judijanto; Nurhikmah Paddiyatu; Rachmawati Novaria; Dewa Oka Suparwata (Westscience Press, 2024)
This study investigates the intricate relationships between environmental policy awareness, community awareness, social support, and community participation in forest conservation programs in West Kalimantan. Utilizing a sample of 150 participants, a quantitative analysis employing Structural Equation Modeling with Partial Least Squares (SEM-PLS) was conducted. The measurement model analysis confirmed the reliability and validity of the survey instrument, and subsequent structural model analysis revealed significant positive relationships between environmental policy awareness, community awareness, social support, and community participation. The findings emphasize the importance of well-crafted environmental policies, informed communities, and robust social support networks in fostering sustainable engagement in forest conservation. These insights carry practical implications for policymakers, environmental organizations, and community leaders, providing a foundation for targeted interventions to enhance conservation initiatives in West Kalimantan.